Ti–Si–C thin films produced by magnetron sputtering : correlation between physical properties, mechanical properties and tribological behavior - Cunha, L. (2010)
Ti–Si–C thin films were deposited onto silicon, stainless steel and high-speed steel substrates by magnetron sputtering, using different chamber configurations. The composition of the produced films was obtained by Electron Probe Micro-Analysis (EPMA) and the structure by X-ray diffraction (XRD). The hardness and residual stresses were obtained by depth-sensing indentation and substrate deflection measurements (using Stoney’s equation), respectively. The tribological behavior of the produced films was studied by pin-on-disc. The increase of the concentration of non-metallic elements (carbon and silicon) caused significant changes in their properties. Structural analysis revealed the possibility of the coexistence of different phases in the prepared films, namely Ti metallic phase ( alpha-Ti or beta-Ti) in the films with higher Ti content. The coatings with highest carbon contents, exhibited mainly a sub-stoichiometric fcc NaCl TiC-type structure. These structural changes were also confirmed by resistivity measurements, whose values ranged from 10E3 Ohm/sq for low non-metal concentration, up to 10E6 Ohm /sq for the highest metalloid concentration. Astrong increase of hardness and residual stresses was observed with the increase of the non-metal concentration in the films. The hardness (H) values ranged between 11 and 27 GPa, with a clear dependence on both crystalline structure and composition features. Following the mechanical behavior, the tribological results showed similar trends, with both friction coefficients and wear revealing also a straight correlation with the composition and crystalline structure of the coatings.